299 Serum Aldosterone and Urine Electrolytes Dynamics in Response to DASH Diet Intervention. (April 2022) - Bielopolski, Dana; Qureshi, Adam; Ronning, Andrea; Tobin, Jonathan N.; Kost, Rhonda G.
Abstract : OBJECTIVES/GOALS: Dietary approach to stop hypertension (DASH) is a proven intervention to treat hypertension. Despite years of research the immediate physiologic response to its implementation was never characterized.This translational trial describes the biological pathway from nutrition through hormons, urine electrolytes and blood pressure reduction. METHODS/STUDY POPULATION: A single center interventional trial. Stage 1 hypertensive otherwise healthy volunteers were admitted for 14-days, transitioning from American style diet to DASH diet. Nutritional habits were assessed with food frequency questionnaires, and menus designed according to the guidelines of the National Heart Blood and Lung Institute (NHBLI) of the National Institute of Health (NIH). Data were collected daily for vital signs, blood and urine. Participants completed two 24-hour ABPM on days 1, 10, and two 24-hour urine collections in parallel. We conducted a follow up visit two weeks after discharge. RESULTS/ANTICIPATED RESULTS: 9 volunteers (78% male, 89% Black individuals) completed the protocol. During an inpatient stay, they consumed a mean daily potassium intake of 5.6 g (Â±0.7g) and 2.6 g (Â±0.3g) of Sodium. Serum Aldosterone increased from day 0 (mean 8.3, range 2.8-18.9) to day 5 (mean 17.8, range 10.2-27.2) after intervention, and decreased on day 11 (mean 11.5, range 4.8-18.2) despite continuous exposure (p-value=0.002). The urine electrolyte ratio of ([Na]/[K]) decreased from a mean of 3.5 before intervention to 1.16 on day 4, creating a statistically significant slope (p-value<0.001). Blood pressure by 24-hour ABPM decreased by 3.7 mmHg systolic BP and 2.3 mmHg diastolic BP from day 1 to 10 for the entire period, and for measures taken during sleep or awake time, assessed separately. DISCUSSION/SIGNIFICANCE: Shifting from a high-sodium low-potassium diet to the opposite composition leads to serial physiological changes that are governed by aldosterone and result in blood pressure reduction. Urine electrolyte ratio reflects nutritional changes within 4 days of transition and should guide clinicians in assessing lifestyle modification adherence.